Transcriptomic and phenotype analysis revealed the role of rpoS in stress resistance and virulence of pathogenic Enterobacter cloacae from Macrobrachium rosenbergii - Gao, Xiaojian; Qian, Qieqi; Zhu, Yujie; Chen, Zhen; Xu, Jingwen; Xu, Wenjing; Jiang, Qun; Wang, Jun; Zhang, Xiaojun (Frontiers in Microbiology, 2022)
Enterobacter cloacae is widely distributed in the aquatic environment, and has been determined as a novel pathogen of various aquatic animals recently. Our previous studies have indicated E. cloacae caused repeated infections in M. rosenbergii, suggesting a high survival ability of the bacteria, and rpoS gene has been known to regulate stress response and virulence of many bacteria. In this study, the E. cloacae-rpoS RNAi strain was constructed by RNAi technology, and the regulation role of rpoS in stress resistance and virulence of E. cloacae was explored by transcriptomic and phenotype analysis. The transcriptome analysis showed a total of 488 differentially expressed genes (DEGs) were identified between rpoS-RNAi and wild-type strains, including 30 up-regulated genes and 458 down-regulated genes, and these down-regulated DEGs were mainly related to environmental response, biofilm formation, bacterial type II secretory system, flagellin, fimbrillin, and chemotactic protein which associated with bacterial survival and virulence. The phenotype changes also showed the E. cloacae-rpoS RNAi strain exhibited significantly decreasing abilities of survival in environmental stresses (starvation, salinity, low pH, and oxidative stress), biofilm production, movement, adhesion to cells, pathogenicity and colonization to M. rosenbergii. These results reveal that rpoS plays an important regulatory role in environmental stress adaptation and virulence of E. cloacae.